Dual Purpose Corn Hybrids’ (Grain-Silage) Performance Assessment in Northeastern Kansas. II. Quality - Felicitas Vignati; Lucas Lingua; W. E. Brown; Ignacio Antonio Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2024)
Dual-purpose corn (Zea mays L.) hybrids are capturing the attention of farmers due to their versatility, as their final use can be chosen as either grain or silage. This versatility emphasizes the importance of understanding the yield and quality performance of these hybrids. This study compared eight dual-purpose corn commercial hybrids’ quality performance. During the 2023 growing season, a dryland field experiment was conducted in Manhattan, Kansas. We analyzed quality at two crop growth stages: before and after the silage process. Dry matter digestibility (DMD) increased after ensiling, mainly due to starch digestibility of ~85 to ~95%. The 6152D1 hybrid led in terms of crude protein (CP) levels before (9.3%) and after ensilage (8.3%). Hybrid 6235D1 showed the lowest conversion efficiency (i.e., lb/t DM) after the silage process. The waxy hybrid 6219WX showed the lowest value of undigested neutral detergent fiber (uNDFD30t) before ensilage (~20%). Differences between hybrids were found regarding the milk per acre index. The hybrid 6219wx achieved the highest value after the silage process (~14 t/a), whereas the hybrid 6219 was the least productive.
Keywords: silage quality; milk per acre index; crude protein; starch; waxy